Investment of Mortgage in Pledged Property - Alwan, Amer (Journal of Legal Sciences, 2023)
The investment of something mortgaged is defined as the creditor’s use of the mortgaged object within the possessed guarantee, so that it will produce certain profit increasing its produce when he uses that for himself or rents it to somebody else or to the creditor himself after discounting his produce from the debt of the mortgagee. The investment of the object mortgaged is the right of the creditor and a commitment imposed upon him simultaneously. If he execute his commitment of investing the mortgaged object which adds a fruit to the produce, the fruit can be discounted from the debt of the mortgaged object; that is to say, a clearing is made between the fruit of the mortgaged object and debt that stands for the object mortgaged. If the creditor violates his commitment, the mortgagee has the right to draw the object mortgaged from his and had it to the juridical person, and the mortgaged has to completely pay the guaranteed debt imposed upon him, so that he can restore the mortgaged object even though before the specified time.